IMPROVING STUDENTS' CONFIDENCE IN SPEAKING BY STORYTELLING TECHNIQUE THROUGH WEBTOON - Tifani, Tifani; Regina, Regina; Wardah, Wardah (FKIP - Universitas Tanjungpura, 2020)
This research was conducted based on the problems found from observation in the teaching and learning process. This research aimed to investigate how the use of storytelling technique through webtoon improved students' confidence in speaking to class X IPS 3 students of SMA Negeri 5 Pontianak Utara in academic year 2018/2019. The method implemented in this research was Classroom Action Research with two cycles. The subjects of the research were 32 students of class X IPS 3. In collecting the data, the writer used observation checklist table, field notes, and questionnaires. The result showed that students’ confidence in speaking improved by using storytelling technique through webtoon. Most of them are active in speaking English in the classroom. In conclusion, storytelling technique through webtoon was useful to help students to improve their confidence in speaking English. Thus, the writer recommends the teacher to use storytelling technique in teaching learning speaking to the student.This research was conducted based on the problems found from observation in the teaching and learning process. This research aimed to investigate how the use of storytelling technique through webtoon improved students’ confidence in speaking to class X IPS 3 students of SMA Negeri 5 Pontianak Utara in academic year 2018/2019. The method implemented in this research was Classroom Action Research with two cycles. The subjects of the research were 32 students of class X IPS 3. In collecting the data, the writer used observation checklist table, field notes, and questionnaires. The result showed that students' confidence in speaking improved by using storytelling technique through webtoon. Most of them are active in speaking English in the classroom. In conclusion, storytelling technique through webtoon was useful to help students to improve their confidence in speaking English. Thus, the writer recommends the teacher to use storytelling technique in teaching learning speaking to the student.